2002
DOI: 10.1063/1.1431270
|View full text |Cite
|
Sign up to set email alerts
|

Polarized atomic orbitals for linear scaling methods

Abstract: We present a modified version of the polarized atomic orbital (PAO) method [M. S. Lee and M. Head-Gordon, J. Chem. Phys. 107, 9085 (1997)] to construct minimal basis sets optimized in the molecular environment. The minimal basis set derives its flexibility from the fact that it is formed as a linear combination of a larger set of atomic orbitals. This approach significantly reduces the number of independent variables to be determined during a calculation, while retaining most of the essential chemistry resulti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 35 publications
1
24
0
Order By: Relevance
“…The inclusion of diffuse functions is mandatory for the description of weak interactions, e.g., hydrogen bonding. Anticipating results and in line with earlier work on polarized atomic orbitals, [23][24][25] it is found that these highly contracted basis sets always lead to well conditioned overlap matrices. In order to derive optimal Gaussian exponents for the primitives and contraction coefficients for the basis sets, parameters are fully optimized based on molecular calculations.…”
Section: Introductionsupporting
confidence: 73%
“…The inclusion of diffuse functions is mandatory for the description of weak interactions, e.g., hydrogen bonding. Anticipating results and in line with earlier work on polarized atomic orbitals, [23][24][25] it is found that these highly contracted basis sets always lead to well conditioned overlap matrices. In order to derive optimal Gaussian exponents for the primitives and contraction coefficients for the basis sets, parameters are fully optimized based on molecular calculations.…”
Section: Introductionsupporting
confidence: 73%
“…The scaling of cost vs. basis size is largely independent of the development of linear scaling (with system size) Fock build algorithms [39][40][41][42][43][44][45] and many diagonalization replacements 46,47 . Moreover, near-complete basis sets are not favored by linear-scaling algorithms, especially when diffuse functions are included, since matrix element sparsity is diminished and the overlap matrix starts to be ill-conditioned, which in turn destroys the sparsity of the density matrix 48,49 . One successful strategy to make large basis KS-DFT calculations more tractable is to compute the full Coulomb (J) and exchange (K) matrices more efficiently by approximating two-electron repulsion integrals (ERIs) with the aid of auxiliary basis functions or grid points.…”
Section: Kohn-sham Density Functional Theorymentioning
confidence: 99%
“…The PAO-SCF energy can be improved using perturbation theory 86 , similar to the dual basis approaches discussed above. The minimal rank of the PAO basis and its atomic locality makes it promising for linearscaling algorithms 49 , but the "double" optimization problem is challenging.…”
Section: Kohn-sham Density Functional Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…͑18͒. Although these basis sets have mainly been used in linearscaling calculations in extended molecules, 23,30 as minimal basis sets, they function in this work primarily as a nonorthogonal basis for the and active spaces in the polyenes. Now, the PAOs are only defined up to a unitary transformation that mixes the orbitals on a given atom.…”
Section: The Polyene Seriesmentioning
confidence: 99%